The Disposition to Sell Winners Too Early and Ride Losers Too Long: Theory and Evidence: Discussion - Constantinides, George M. (Journal of Finance, 1985)
George M. Constantinides, The Disposition to Sell Winners Too Early and Ride Losers Too Long: Theory and Evidence: Discussion, The Journal of Finance, Vol. 40, No. 3, Papers and Proceedings of the Forty-Third Annual Meeting American Finance Association, Dallas, Texas, December 28-30, 1984 (Jul., 1985), pp. 791-792